2004
DOI: 10.1097/01.mph.0000141348.62532.73
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Compound-Related Ototoxicity in Children

Abstract: Children treated with cisplatin at cumulative doses approaching 400 mg/m require long-term surveillance to avoid overlooking hearing deficits. Carboplatin, at a standard dose, does not appear to be a significant risk factor for ototoxicity even in patients who have already been treated with cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(86 citation statements)
references
References 42 publications
3
78
0
5
Order By: Relevance
“…CDDP is one of the most effective and widely used cytotoxic agents for the treatment of adult and pediatric malignancies [1,2,3,4,5,6]. Ototoxicity, neurotoxicity and nephrotoxicity are major dose-limiting side effects of CDDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDDP is one of the most effective and widely used cytotoxic agents for the treatment of adult and pediatric malignancies [1,2,3,4,5,6]. Ototoxicity, neurotoxicity and nephrotoxicity are major dose-limiting side effects of CDDP.…”
Section: Discussionmentioning
confidence: 99%
“…Ototoxicity, neurotoxicity and nephrotoxicity are major dose-limiting side effects of CDDP. CDDP-induced ototoxicity is characterized by bilateral, usually permanent, high-frequency sensorineural hearing loss that can progress to the lower frequencies [2,3,4,5,6]. There is an individual susceptibility to CDDP ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…48;49 Ototoxicity following these exposures first affects higher frequencies (>4 KHz) and with continued exposure can progress to involve lower (speech) frequencies. 50 Hearing loss also can continue to worsen after completion of therapy and be accompanied by tinnitus and vertigo. 50 Radiation alone with cumulative cochlear dose ≥30 Gy (inclusive of any TBI or cranial radiation) also is associated with sensorineural hearing loss, which may develop and/or progress years after exposure.…”
Section: Sensorymentioning
confidence: 99%
“…50 Hearing loss also can continue to worsen after completion of therapy and be accompanied by tinnitus and vertigo. 50 Radiation alone with cumulative cochlear dose ≥30 Gy (inclusive of any TBI or cranial radiation) also is associated with sensorineural hearing loss, which may develop and/or progress years after exposure. 48;51 Additionally, radiotherapy also can result in conductive hearing loss, tympanosclerosis, otosclerosis, and Eustachian tube dysfunction.…”
Section: Sensorymentioning
confidence: 99%
“…In contrast, Stern and Bunin [11] found that ototoxic complications from carboplatin chemotherapy were rare and mild in severity. Other studies have also reported a lack of ototoxic side effects in children receiving carboplatin [12,13]. Factors that may potentiate carboplatin ototoxicity include prior exposure to cisplatin or other ototoxic medications and high dosages of carboplatin [7,10,14].…”
Section: Introductionmentioning
confidence: 99%